Unexpected benzene oxidation in collisions with superoxide anions - Carlos Guerra (Nature Portfolio, 2021)
Abstract Superoxide anions colliding with benzene molecules at impact energies from 200 to 900 eV are reported for the first time to form massive complexes. With the aid of quantum chemistry calculations, we propose a mechanism in which a sudden double ionization of benzene and the subsequent electrostatic attraction between the dication and the anion form a stable covalently bonded C6H6O2 + molecule, that evolves towards the formation of benzene-diol conformers. These findings lend support to a model presenting a new high energy anion-driven chemistry as an alternative way to form complex molecules.